ANALISIS PENGARUH GAYA KEPEMIMPINAN OTOKRATIS, DEMOKRATIK DAN LAISSEZ FAIRE TERHADAP PENINGKATAN KINERJA PERANGKAT DESA - Lona Chinsia Alfattama; Andiko Sri Kuncoro (Universitas Tulungagung, 2023)
The success of village government leaders in influencing their village apparatus, one ofwhich can be determined by the leadership style used. The more the leadership style usedis favored by subordinates, the easier it is for leaders to influence and mobilizesubordinates. So that leaders can move their subordinates to achieve predeterminedorganizational goals. The purpose of the study was to determine the effect of autocratic,democratic and leissez faire leadership styles on improving the performance of villageofficials in the Boyolangu District Area both simultaneously and partially. The resultsshowed that simultaneously (simultaneously) the autocratic, democratic, and laissez faireleadership style variables had a positive and significant effect on improving theperformance of village officials in Boyolangu District, Tulungagung. This is evidencedby the value of Fcount (361.619) greater than Ftable (2.38) or Fsig (0.000) < α (0.05).Autocratic leadership style has a positive and significant effect on improving theperformance of village officials in Boyolangu District, Tulungagung. This is evidencedby the value of tcount (3.818) greater than ttable (2.72) or tsig (0.000) less than α (0.05).Democratic leadership style has a positive and significant effect on improving theperformance of village officials in Boyolangu District, Tulungagung. This is evidencedby the tcount value (6.486) is greater than the ttable (2.72) or tsig (0.000) is smaller thanα (0.05). The laissez faire leadership style has a positive and significant effect onimproving the performance of village officials in Boyolangu District, Tulungagung. Thisis evidenced by the value of tcount (3.332) greater than ttable (2.72) or tsig (0.001)smaller than α (0.05). Democratic leadership style has the most dominant influencecompared to other independent variables. This is evidenced by the amount of Partial Rfor the democratic leadership style variable has the greatest value compared to othervariables (autocratic leadership style = 0.389, democratic = 0.582, and laissez faire =0.345).